PENERAPAN HIGIENE, SANITASI DAN KESELAMATAN KERJA DI DAPUR - Mochammad Musafa’ul Anam; Muhammad Danang Setioko; Aprillia Rahmadian (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
Sanitation and hygiene is a preventive effort that aims to prevent disease, especially in the environment and individuals to protect themselves from disease. This of course cannot be separated from our efforts in maintaining safety and health both in the environment where we live and in the workplace, especially in the kitchen. As an effort to improve the quality and quality of production, Ivanna Catering requires a guideline in implementing Hygiene, Sanitation and Work Safety in the Kitchen. The preparation of Standard Operating Procedures in the form of guidelines aims to assist in carrying out the functions of a professional and safe workplace. Of course, if food or drinks are processed without hygiene and sanitation standards, it can cause several diseases for consumers. In addition, by not applying good hygiene and sanitation standards, it may endanger employees.